Implementasi Kebijakan Larangan Penangkapan Ikan pada Hari Tertentu sebagai Upaya Mencapai Tujuan Pembangunan Berkelanjutan: Kehidupan Bawah Laut - Beltahmamero Simamora; Indra Muda; Evi Yunita Kurniaty; Gustami Harahap; Agung Suharyanto (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
This research aims to explore and understand more deeply the implementation of the no-fishing policy as an effort to achieve sustainable development goals for life below water. The research method uses qualitative with a descriptive approach with the aim of building meaning based on the views of participants. Data collection is carried out through three stages: observation by directly observing fishing activities and comparing them to the activities of the day of the fishing ban, in-depth interview stages by meeting informants and the literature study stage is carried out by collecting research results that are closely related to the research. The determination of informants was carried out purposively with the criteria of the Sabang City Community, who work as Fishermen, fishermen who know about the no fishing policy, ship-owning financiers who are closely related to fishing operations, and traditional representatives of the laot customary commander. The research findings of the communication stage, which originally prohibited fishing as part of the culture, was changed into a rule with a legal umbrella in Qanun No. 7 of 2010 concerning fisheries. The resources stage was carried out by forming an institution in charge of supervising and enforcing customary law rules, namely Panglima laot, which was further reinforced by the issuance of Qanun No. 10 of 2008 concerning the role of customary institutions. The disposition stage provides social sanctions in the form of ostracism and gives negative stigma to strict sanctions in the form of confiscation of catches and boats for three to seven days; the bureaucratic structure stage reinforces the authority of customary law and the role of Panglima laot as stated in Qanun No. 10 of 2008 and Qanun No. 7 of 2010.